Application Methods of Linear Feedback Control on the Modified Lorenz 3D Chaotic System - Mahasin Thabit Younis; Zeena N. Al-kateeb (Tikrit Journal of Pure Science, 2020)
In this paper we using a linear feedback control methods on the Lorenz modified 3D system. we used the dynamical analysis system to find critical points, eigenvalues, and for stability, the Jacobi matrix, to investigate some dynamical behaviors of the system to find stability regions of the system in all methods used to suppress the originally unstable behavior of this system. The necessary and sufficient condition for suppression of unstable behavior for this system is getting positive feedback coefficient. Theoretical analysis and numerical simulation proved that the results obtained.